Development of chloroplast markers for Japanese and snow camellias. Issue 1 (6th January 2015) - Ueno, Saneyoshi; Taguchi, Yuriko; Tsumura, Yoshihiko
Abstract: Eight chloroplast markers were developed from Japanese and snow camellia ( Camellia japonica and C. rusticana ). Six markers were based on mononucleotide repeats, while the other two resulted from indels of larger units. Polymorphisms were screened using 15 individuals from all over the Japanese archipelago, including C. japonica, C. japonica var. macrocarpa, C. japonica var. hozanensis, and C. rusticana . Polymorphisms within a single population were searched in 22 and 26 individuals of C. japonica and C. rusticana, respectively. The number of alleles per locus ranged from two to three, resulting in eight haplotypes, two of which were specific to C. rusticana . No polymorphisms were detected within a single population for both C. japonica and C. rusticana . The eight markers developed in the present study will be useful for analyzing the genetic diversity and tracing maternal origins of Japanese and snow camellias.